Extraction and Application of Natural Rutin From Sophora japonica to Prepare the Novel Fluorescent Sensor for Detection of Copper Ions - Yang, Shilong; Sun, Lu; Song, Zhiwen; Xu, Li (Frontiers in Bioengineering and Biotechnology, 2021)
Rutin (R), a representative flavonoid in various biomass, can be used to prepare different fluorescent sensor in environmental, biological and medical fields. In this work, the natural R in Sophora japonica was extracted and purified to prepare fluorescent sensor for highly sensitive and selective detection of copper ions. Results showed that neat R had no obvious fluorescent emission peak in PBS buffer solution. When it was complexed with (2-hydroxypropyl)-β-cyclodextrin (CD) in the buffer solution, the fluorescent emission intensity was significantly increased due to the formed R-CD inclusion complex. In addition, the formed R-CD inclusion complex could act as fluorescent sensor for detecting copper ions by the mechanism of quenching fluorescent emission intensity when R-CD was bound with copper ions. The binding constant value for R-CD with copper ions was 1.33×106, which can quantify the copper ions concentration with a linear range of 1.0× 10-8-1.7 × 10-6 mol·L-1 and the detection limit of 3.5 × 10-8 mol·L-1. This work showed the prepared R-CD inclusion complex had the ability of high selectivity and sensitivity toward copper ions, which can be further to apply in determining copper ions in different fields.